THE INDONESIAN GOVERNMENT’S STRATEGY IN MITIGATING THE IMPACT OF GLOBAL CONFLICTS - Khairunnisa Simbolon; Gita Karisma (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Indonesia’s national food security is at a critical point due to global supply chain disruptions, fluctuations in strategic commodity prices, and the impact of geopolitical conflicts. This analysis shows that the government’s response emphasizes a combination of domestic strategies and international diplomacy to mitigate these risks. At the domestic level, policies are directed toward food diversification, import substitution, agricultural modernization, optimization of idle land, and strengthening food reserves through food estate programs. However, their effectiveness is hampered by limited infrastructure, technological gaps, and potential environmental degradation. Meanwhile, at the international level, Indonesia is intensifying cooperation through ASEAN, BRICS, and other multilateral forums to secure supplies, expand financing access, and promote technology transfer. This approach aligns with the four pillars of food security defined by the FAO: availability, access, utilization, and stability, which are translated into policies on sustainable production, strengthened distribution and supply chains, nutrition improvement, and guaranteed food access for all social groups. This study underscores that the success of these strategies depends on consistent cross-sectoral implementation and policy synergy at local, regional, and global levels. The findings contribute to the food security literature by highlighting Indonesia’s strategic role in diplomacy to integrate domestic agendas with international cooperation, while also offering an adaptive policy framework in response to geopolitical dynamics and climate change.